Are one-stop centres an appropriate model to deliver services to sexually abused children in urban Malawi? - Yabwile Mulambia; Aaron J. Miller; Geraldine MacDonald; Neil Kennedy (BMC, 2018)
Abstract Background The Republic of Malawi is creating a country-wide system of 28 One-Stop Centres (known as 'Chikwanekwanes' - 'everything under one roof') to provide medical, legal and psychosocial services for survivors of child maltreatment and adult intimate partner violence. No formal evaluation of the utility of such services has ever been undertaken. This study focused on the experiences of the families served at the country's first Chikwanekwane in the large, urban city of Blantyre. Methods One hundred seven families were surveyed in their home three months after their initial evaluation for sexual abuse at the Blantyre One Stop Centre, and 25 families received a longer interview. The survey was designed to inquire what types of initial evaluation and follow-up services the children received from the medical, legal and social welfare services. Results All 107 received an initial medical exam and HIV testing, and 83% received a follow-up HIV test by 3 months; 80.2% were seen by a social welfare worker on the initial visit, and 29% had a home visit by 3 months; 84% were seen by a therapist at the initial visit, and 12% returned for further treatment; 95.3% had an initial police report and 27.1% ended in a criminal conviction for child sexual abuse. Most of the families were satisfied with the service they received, but a quarter of the families were not satisfied with the law enforcement response, and 2% were not happy with the medical assessment. Conclusions: Although a perception of corruption or negligence by police may discourage use of service, we believe that the One-Stop model is an appropriate means to deliver high quality care to survivors of abuse in Malawi.